Usar la palabra política en vano. Blasfemia, parodia e ironía como reapropiaciones de lo político* - Martínez de Albéniz, Iñaki (Foro Interno, 2005)
To take God’s name in vane – that is the definition of blasphemy. The same could be said of politics – to take the name of politics in vane. Today political language games (and also word-play) involve blasphemy, euphemism (Émile Benveniste), zombie concepts (Ulrich Beck), parodies (Judith Butler) and irony (Richard Rorty). This article deals with misuses of the term politics, uses that are prohibited by the discourse police (Michel Foucault) –political philosophy, political theory, political sciencebecause of their vacuity, that is, their enunciation in a vacuum. In this respect I argue that far from being a useless employment of the word politics, certain social actors reappropriate the term in novel use-contexts and resignify it either through saturation, when a type of panpoliticism is proposed (everything is political), or by declaring that it is not a functional term.
Keywords: Political theory; rhetoric; discourse analysis; language games; performativity